Genetic variants in CDC42 and NXPH1 as susceptibility factors for constipation and diarrhoea predominant irritable bowel syndrome. Issue 7 (16th September 2013) - Wouters, Mira M; Lambrechts, Diether; Knapp, Michael; Cleynen, Isabelle; Whorwell, Peter; Agréus, Lars; Dlugosz, Aldona; Schmidt, Peter Thelin; Halfvarson, Jonas; Simrén, Magnus; Ohlsson, Bodil; Karling, Pontus; et al.
Abstract : Objective: The complex genetic aetiology underlying irritable bowel syndrome (IBS) needs to be assessed in large-scale genetic studies. Two independent IBS cohorts were genotyped to assess whether genetic variability in immune, neuronal and barrier integrity genes is associated with IBS. Design: 384 single nucleotide polymorphisms (SNPs) covering 270 genes were genotyped in an exploratory cohort (935 IBS patients, 639 controls). 33 SNPs with Puncorrected <0.05 were validated in an independent set of 497 patients and 887 controls. Genotype distributions of single SNPs were assessed using an additive genetic model in IBS and clinical subtypes, IBS-C and IBS-D, both in individual and combined cohorts. Trait anxiety (N=614 patients, 533 controls), lifetime depression (N=654 patients, 533 controls) and mRNA expression in rectal biopsies (N=22 patients, 29 controls) were correlated with SNP genotypes. Results: Two SNPs associated independently in the exploratory and validation cohort: rs17837965- CDC42 with IBS-C (ORexploratory =1.59 (1.05 to 1.76); ORvalidation =1.76 (1.03 to 3.01)) and rs2349775- NXPH1 with IBS-D (ORexploratory =1.28 (1.06 to 1.56); ORvalidation =1.42 (1.08 to 1.88)). When combining both cohorts, the association of rs2349775 withstood post hoc correction for multiple testing in the IBS-D subgroup. Additionally, three SNPs in immune-related genes (rs1464510- LPP, rs1881457- IL13, rs2104286- IL2RA ), one SNP in a neuronal gene (rs2349775- NXPH1 ) and two SNPs in epithelial genes (rs245051-S LC26A2, rs17837965- CDC42 ) were weakly associated with total-IBS (Puncorrected <0.05). At the functional level, rs1881457 increased IL13 mRNA levels, whereas anxiety and depression scores did not correlate with rs2349775- NXPH1 . Conclusions: Rs2349775 ( NXPH1 ) and rs17837965 ( CDC42 ) were associated with IBS-D and IBS-C, respectively, in two independent cohorts. Further studies are warranted to validate our findings and to determine the mechanisms underlying IBS pathophysiology.